If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 5x = 3x + -13 Reorder the terms: 9 + 5x = -13 + 3x Solving 9 + 5x = -13 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + 5x + -3x = -13 + 3x + -3x Combine like terms: 5x + -3x = 2x 9 + 2x = -13 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + 2x = -13 + 0 9 + 2x = -13 Add '-9' to each side of the equation. 9 + -9 + 2x = -13 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = -13 + -9 2x = -13 + -9 Combine like terms: -13 + -9 = -22 2x = -22 Divide each side by '2'. x = -11 Simplifying x = -11
| 6.78a-5.2=4.33a+2.15 | | 2x^2+30-12=0 | | (x+20)+3=180 | | 0.5=35 | | -3x-5(x+3)=-(1+x) | | -18-4y-y=13 | | -6c-4-5c= | | 9(x-3)=-27+9x | | 2x-57= | | -5u-2=3u^2 | | 5x+6=x+4 | | (x+20)+(210-3x)+x=180 | | 0.9(6x+12)=1.6-(x+2) | | 4n+3n=21 | | 2d+7+3d=-41 | | 2.5y+8= | | 2x+8=38+5x | | 4+2a=3(s-2)+1 | | 1.9(g-9.1)=-7.22 | | .5j=5 | | 11.54-d=6.54 | | 15.8=1.2(r-4)+9.8 | | 8x^2=4-7x | | 6=-4-2 | | 6+6x(x+8)= | | 5(9-11)=m-8 | | 2y=2y+40 | | -k+3=-4 | | 8m=-64 | | 4y+40=10y-20 | | U^2=15u+36 | | 21-42=3(x-2)-6 |